The Unbearable Arabness of Being: Anti-Arab Racisms in the Human Rights Sector - Fatima Ahdash (22565390) (2025)
One unseasonably cold night in the middle of August 1997, I arrived in the UK with my parents and siblings as a refugee from Libya. Even though I was very young, I understood intimately and painfully exactly what the perilous journey my family had made meant. My parents were honest: we were escaping the Libyan regime’s violent crackdown on all forms of political dissent—which had already claimed the lives of many relatives and friends—and we were now exiles, unlikely ever to return ‘home.’ Other Information Published in: Feminist Legal Studies License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10691-025-09579-y